Early parenteral feeding of amino acids. Issue 10 (October 1989) - Saini, J; MacMahon, P; Morgan, J B; Kovar, I Z
Abstract : Serial 24 hour balance studies of nitrogen and energy were carried out over 10 days in two groups of ventilator dependent preterm infants, of comparable weight and gestational age. In one group (n = 10) a parenteral amino acid source (Vamin 9) was started within 24 hours of birth, and in the other group (n = 11) it was not started until 72 hours. The feeding protocol was otherwise identical. The nitrogen intake (286 compared with 21 mg/kg/day), energy intake (188 compared with 151 kJ), and nitrogen retention (120 compared with -133 mg/kg/day), were all significantly higher during the first three days of life in the group in which the amino acid solution was started early. There were no differences by 7-10 days. The early introduction of amino acids improves the early nutritional state of sick preterm infants.